The art and science of book publishing - Bailey, Herbert Smith (University of Texas Press, 1970)
Now back in print, this volume discusses with authority every aspect of the editorial and financial operations of the modern publishing house. Unlike other books on this subject, The Art and Science of Book Publishing is distinguished by its conceptual approach, viewing the publishing house as a whole, emphasizing both its external and internal environments. The book proceeds through the basic activities of publishing to a pragmatic analysis of decisions on individual books and operations of the publishing house as a whole. This standard resource of the publishing industry will be welcomed by beginners, who will find the book eye–opening, as well as veterans who will see their work in a new light.